THE INFLUENCES OF PEER FEEDBACK IN IMPROVING EFL LEARNERS’ WRITING PERFORMANCES - Wijaya, Kristian Florensio (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2024)
Enhancing EFL learners’ writing performances should not solely rely on one-shot feedback imparted by second language educationalists but rather a joint endeavor where collaborative and mutual feedback exists to insistently support the ongoing writing learning enterprises. The further usage of peer feedback fully suits the aforementioned writing learning aspiration in which EFL learners collaboratively address a vast variety of beneficial suggestions, comments, and advice intended for the betterment of their writing performances. This present small-scale qualitative study was manifested in the form of an annotated bibliography review to comprehensively unravel the particular impacts of peer feedback in elevating EFL learners’ writing performances. To fulfill this major study objective, the researcher employed a document analysis method in reviewing the previously generated research results to yield more credible and understandable research results. To ascertain the relevance and applicability of the reviewed research results, the researcher also selected 10 prior peer feedback and writing investigations. The research results revealed that through the constant employment of peer feedback, worldwide EFL learners have progressively transfigured into more proactive, viable, and proficient writers since they conducted more efficient writing revisions in accord with their learning counterparts’ useful comments.